Wake the dawn : a novel - Snelling, Lauraine (FaithWords, 2013)
When a natural disaster threatens to destroy lives in the small mountain town of Pineville, Minnesota, Doctor Esther Hanson struggles to help her patients without giving in to overwhelming emotions triggered by a long-suppressed memory and U.S. Border Patrol agent Ben James, grieving the tragic loss of his wife, rushes an an abandoned baby to Esther's clinic. Brought together by the life of a child, Ben and Esther become each other's reason to change.